La filosofia della prassi e la critica al doppio revisionismo di Marx nei Quaderni di Gramsci - Schlesener, Anita Helena (International Gramsci Journal, 2024)
This article is the result of research in development and presents a reflection on the concept of the “philosophy of praxis” in Gramsci’s Prison Notebooks. The theme involved questions regarding the method, a gnoseology or theory of knowledge and the articulation between economics, politics and philosophy. The first part discusses the limits of liberalism in its formal structure; the second explains the articulation between economics, politics and philosophy; the third takes up the criticism of the double revisionism of Marx from Notebook 4. The main targets of Gramsci’s critique of this “double revisionism” of his time are, on the one hand, the followers of Max Adler and others of the “Austro-Marxist” school, influenced by philosophically idealist currents (neo-Kantianism in particular), and, on the other, the mechanicist and deterministic current represented by Bukharin and others in the Soviet Union.